ANALISIS KEMAMPUAN PEMECAHAN MASALAH DALAM MENYELESAIKAN SOAL CERITA SPLDV BERDASARKAN LANGKAH - - Husain, Zubair; F. Kaunang , Derel; G. Maukar, Marvel (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The study's objectives is to outline the processes of Polya's problem-solving method for addressing story problems involving a system of linear equations with two variables while accounting for the students' adversity quotient (AQ). The study was carried out at SMP Negeri 2 Langowan during the odd semester of the 2021–2022 academic year. For this study, a qualitative descriptive methodology was used. Three eighth-graders from SMP Negeri 2 Langowan served as the study's subjects. Based on their aptitude for problem-solving and level of adversity, they were classified as climbers, campers, or quitters. Exams, interviews, and questionnaires were the methods of data collecting. Based on the research's analyzed findings, it was discovered that when using Polya's problem-solving steps to solve story problems pertaining to a system of linear equations with two variables, students' problem-solving skills could be categorized into three groups based on their ability to overcome adversity: climbers, campers, and quitters. Students with the AQ climber type, master every problem-solving indicator. Students with camper-type AQ, on the other hand, are able to understand three problem solvings. Students with quitter-type AQ, on the other hand, can only meet one problem-solver.